(-21)-t/3=-6

Simple and best practice solution for (-21)-t/3=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-21)-t/3=-6 equation:


t in (-oo:+oo)

-(t/3)-21 = -6 // + 6

6-(t/3)-21 = 0

-1/3*t-15 = 0 // + 15

-1/3*t = 15 // : -1/3

t = 15/(-1/3)

t = -45

t = -45

See similar equations:

| (-21)-t/3=-6 | | 26.5+x=42 | | p-13=6 | | -n+2=5n+7 | | 6+6x=20+4x | | 4-15=4+14 | | 7y-1=2(y+3) | | 3x+6=-25 | | 11/4+a=27/10 | | 5(-3+6n)=33+6n | | 12x^2-64=-x^4 | | 3bx-2=4ax+3 | | 7th-4=10t+14 | | -(2p+4)+8p=-p-18 | | -80+4y=4 | | 6-4r+3r=13 | | -7-3i+8-3i=0 | | 4w^2+4w+1=49 | | .5(x+40)+.1x=29 | | -8x+4=4 | | 16(x+1)=4(4x+9)-20 | | a/6+4a/8-1/3=a+3/4 | | 7x+20=-13 | | x+30=45 | | 7(2c-5)=6 | | 3(x-3)+5x=4(2x+4)-8 | | 65=5x+12 | | 7+y=-13 | | 72c-5=6 | | y-240=6(x-20) | | 4x+3-5=2x | | 4(y-5)(2y+3)=0 |

Equations solver categories